Identification of evidence by engineering undergraduates and pre-service science teachers in an argumentation activity - Cano-Iglesias, María José; Blanco-López, Ángel; Franco-Mariscal, Antonio Joaquín (My University, 2019)
Scientific argumentation is considered as one of the general competencies that engineering students must achieve. This paper analyses the capacity to identify evidence in an argumentation activity on characteristics of materials, developed with 46 engineering undergraduates of the second year of the Degree in Industrial Technologies Engineering and 81 pre-service science teachers of the University of Malaga (Malaga, Spain). These pre-service science teachers studied a Master's Degree in Secondary Education and were classified for this study in two groups depending on whether or not their previous degree was related to the knowledge necessary to solve the activity. The activity proposes to argue the choice of a bicycle according to the material of manufacture (steel or aluminium), focusing this paper on the analysis of the evidence shown in their arguments. A number of evidence, their type, their quality in terms of the level of adequacy and precision, and the inclusion or not of personal ideas, were considered as dimensions. The results show that engineering undergraduates are capable of offering arguments with a greater number of evidence and of different types (economic, physical-chemical and mechanical) as opposed to pre-service science teachers. On the contrary, pre-service teachers offer arguments with a better quality of evidence than undergraduates. Pre-service science teachers from degrees unrelated to the activity used a great number of personal ideas when arguing. These results highlight the need to continue training both undergraduates and pre-service teachers so that they can argue in their profession in the best possible way.
Keywords: Toma de decisiones; initial teacher education (pre-service); evidence-based approaches; decision making